Eletrodinâmica no ensino médio : uma sequência didática apoiada nas tecnologias e na experimentação - Silva, Marcelo da (2016)
The research, which is part of information, communication, and interaction technologies applied to Sciences and Math teaching, aims to investigate the relevance of a didactic proposal that involves not only rescuing previous knowledge, but also the use of experimental activities, simulators, and other technological resources in the study of electrical circuits. The main question of this study is to what extent do didactic sequences based on different strategic resources contribute to approaching students to Physics?; thus, aiming to develop a didactic sequence that uses different strategic resources for the study of electrical circuits, analyzing their relevance in terms of generating interest and motivation of students to learn Physics. Hence, the present Master s thesis was organized initially presenting a reflection on learning in the cognitive perspective by David Ausubel, Jean Piaget, and Lev S. Vygotsky, and then presenting the movements of alternative conceptions and conceptual change. It also addresses the use of experimentation as a teaching strategy and explains aspects inherent to the use of digital technologies as a support element for classes, highlighting the contribution of the use of virtual simulators in Physics teaching. Such didactic sequence was structured in twelve meetings, which addressed the study of electrodynamics using videos, simulators, and experimental activities, among other different didactic tools. The didactic proposal was applied in a class of thirty-one students of the third year of high school, in a public school of the city of Passo Fundo, RS, Brazil. In order to contribute to the work of other teachers, the different didactic tools used in the didactic sequence, as well as the written material and other didactic resources, were combined in a website that forms the educational product of this thesis, which is available at the website of the Post-graduation program and may be accessed free of charge. Lastly, data collection, which aimed to answer the initial question, was performed through three research instruments: written records made by the researcher of each activity performed, record of experimental classes, and interview with students after the conclusion of the didactic sequence. These three instruments allowed inferring that the use of different tools related to experiential situations of students, and by inserting the use of technology, works as a motivator for students to perform the activities, as well as stimulating their participation during Physics classes.